SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN PEMILIHAN LAPTOP DENGAN METODE FUZZY TAHANI BERBASIS WEB - Zekson Arizona Matondang; Pilipus Tarigan (UPPM, 2020)
Tablet computer shops as tablet computer sales continue to follow the development of tablet computer technology to meet the needs of tablet computer buyers, where consumers as tablet computer buyers generally always have considerations or factors before making a decision, for example price, brand , the screen size, memory, hard disk, or features available on the tablet computer and other factors. To be able to help with this, it needs to be supported into a computerized decision support system. In addition to providing information, a decision support system can also help provide various alternatives that can be taken in the decision-making process. Fuzzy logic is an appropriate way to map an input space into an output space. Most people think that fuzzy logic is something very complicated and unpleasant, but once someone gets to know it, they will certainly be interested and become a newcomer to learn it